2021
DOI: 10.1021/acs.jmedchem.1c01601
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Highly Potent, Selective, and Bioavailable SGK1 Protein Kinase Inhibitors for the Treatment of Osteoarthritis

Abstract: The serine/threonine kinase SGK1 is an activator of the β-catenin pathway and a powerful stimulator of cartilage degradation that is found to be upregulated under genomic control in diseased osteoarthritic cartilage. Today, no oral diseasemodifying treatments are available and chronic treatment in this indication sets high requirements for the drug selectivity, pharmacokinetic, and safety profile. We describe the identification of a highly selective druglike 1H-pyrazolo[3,4-d]pyrimidine SGK1 inhibitor 17a that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 52 publications
(74 reference statements)
0
15
0
Order By: Relevance
“…The ability of Sanofi-14h treatment to inhibit activation of TBK1 led us to examine a panel of SGK and AGC family kinase inhibitors for their effects on STING-induced signaling. In this regard, we synthesized Sanofi 17a 31 , a derivative of Sanofi-14h, which preferentially targets SGK1 (Fig. 5A) 31 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ability of Sanofi-14h treatment to inhibit activation of TBK1 led us to examine a panel of SGK and AGC family kinase inhibitors for their effects on STING-induced signaling. In this regard, we synthesized Sanofi 17a 31 , a derivative of Sanofi-14h, which preferentially targets SGK1 (Fig. 5A) 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we synthesized Sanofi 17a 31 , a derivative of Sanofi-14h, which preferentially targets SGK1 (Fig. 5A) 31 . We found that Sanofi-14h, Sanofi-17a, GSK650394, and SI113 all inhibited STING-driven IRF3 activation in a reporter assay with similar potency.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations